Mitochondrial-specific autophagy linked to mitochondrial dysfunction following traumatic freeze injury in mice - Nichenko, Anna S. (Am J Physiol Cell Physiol, 2020)
The objective of this study was to interrogate the link between mitochondrial dysfunction and mitochondrial-specific autophagy in skeletal muscle. C57BL/6J mice were used to establish a time course of mitochondrial function and autophagy induction after fatigue (n = 12), eccentric contraction-induced injury (n = 20), or traumatic freeze injury (FI, n = 28); only FI resulted in a combination of mitochondrial dysfunction, i.e., decreased mitochondrial respiration, and autophagy induction. Moving forward, we tested the hypothesis that mitochondrial-specific autophagy is important for the timely recovery of mitochondrial function after FI. Following FI, there is a significant increase in several mitochondrial-specific autophagy-related protein contents including dynamin-related protein 1 (Drp1), BCL1 interacting protein (BNIP3), Pink1, and Parkin (~2-fold, P < 0.02). Also, mitochondrial-enriched fractions from FI muscles showed microtubule-associated protein light chain B1 (LC3)II colocalization suggesting autophagosome assembly around the damaged mitochondrial. Unc-51 like autophagy activating kinase (Ulk1) is considered necessary for mitochondrial-specific autophagy and herein we utilized a mouse model with Ulk1 deficiency in adult skeletal muscle (myogenin-Cre). While Ulk1 knockouts had contractile weakness compared with littermate controls (−27%, P < 0.02), the recovery of mitochondrial function was not different, and this may be due in part to a partial rescue of Ulk1 protein content within the regenerating muscle tissue of knockouts from differentiated satellite cells in which Ulk1 was not genetically altered via myogenin-Cre. Lastly, autophagy flux was significantly less in injured versus uninjured muscles (−26%, P < 0.02) despite the increase in autophagy-related protein content. This suggests autophagy flux is not upregulated to match increases in autophagy machinery after injury and represents a potential bottleneck in the clearance of damaged mitochondria by autophagy.